Antiviral Compounds to Address Influenza Pandemics: An Update from 2016-2022 - Romeo, Roberto; Legnani, Laura; Chiacchio, Maria A.; Giofré, Salvatore V.; Iannazzo, Daniela (Current Medicinal Chemistry, 2024)
In recent decades, the world has gained experience of the dangerous effects of pandemic events caused by emerging respiratory viruses. In particular, annual epidemics of influenza are responsible for severe illness and deaths. Even if conventional influenza vaccines represent the most effective tool for preventing virus infections, they are not completely effective in patients with severe chronic disease and immunocompromised and new small molecules have emerged to prevent and control the influenza viruses. Thus, the attention of chemists is continuously focused on the synthesis of new antiviral drugs able to interact with the different molecular targets involved in the virus replication cycle. To date, different classes of influenza viruses inhibitors able to target neuraminidase enzyme, hemagglutinin protein, Matrix-2 (M2) protein ion channel, nucleoprotein or RNAdependent RNA polymerase have been synthesized using several synthetic strategies comprising the chemical modification of currently used drugs. The best results, in terms of inhibitory activity, are in the nanomolar range and have been obtained from the chemical modification of clinically used drugs such as Peramivir, Zanamivir, Oseltamir, Rimantadine, as well as sialylated molecules, and hydroxypyridinone derivatives. The aim of this review is to report, covering the period 2016-2022, the most recent routes related to the synthesis of effective influenza virus inhibitors.
Keywords: hemagglutinin